PENGARUH RATIFIKASI KONVENSI HAK ANAK TERHADAP PERLINDUNGAN HAK ATAS KELANGSUNGAN HIDUP ANAK BALITA PENDERITA GIZI BURUK DI PROPINSI DAERAH ISTIMEWA YOGYAKARTA (DIY) - , TITO ANGGI DOLLY; , Endang Purwaningsih, S.H., M.H. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This research entitled \"The Impact of the Ratification of the Convention on the Rights of the Child Towards the Protection of the Rights to Survival of Child with Malnutrition in the Special Region of Yogyakarta Province (DIY)\" aims to understand the influence of the ratification of the Convention on the Rights of the Child (hereinafter reffered to as CRC) 1989 by Indonesia towards the protection of the rights to survival of severely malnourished children under the age of five, either through juridical follow-up after the ratification and/or through the implementation of the values of protection of the rights of the child stated in CRC. This research is a juridical research study. The resources of research in this study was collected using the literature research to obtain primary legal materials, secondary legal materials, and non-legal materials. The method used in this research is the analysis of law approach, the comparison approach and the approach of the cases. Based on the results in the discussion, the results of this study are: First, that the factors causing malnutrition in the Special Region Province is very complex, each factors are interconnected, namely poverty, child care pattern, nutrition intake for children, and the availability of health facilities. Second, that the ratification of CRC by Indonesia brought a good impact for the protection of children's rights including the right to survival for children with malnutrition under the age of five that can be seen from the government efforts through legal instruments made after ratification, which is in line with the values contained in CRC and its implementation in real actions to overcome the problem of malnutrition. Keywords: Convention on the Rights of the Child, CRC, The Survival Rights, Malnutrition